The Influence of Independence, Motivation, and Understanding of Entrepreneurship on Entrepreneurial Interest in Vocational Students - Darmuji, Darmuji; Fatiyah, Husnul (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2021)
This research was conducted to determine the influence of independence, motivation, and understanding of entrepreneurship on entrepreneurial interest in Vocational students. The methods used by researchers are quantitative and verification methods. The population taken for this study came from 4 Study Programs Accounting, Electronic Engineering, Electrical Engineering, and Mechanical Engineering at one of Vocational School and a total of 250 respondents who were taken by using sampling techniques. There are two data in this study, namely primary data and secondary data collected. The researcher collected the data by using an online questionnaire distributed to all the participants. The data that has been obtained, then analysed using multiple regression tests, multiple correlation tests, and verification analysed for each and between variables. This study shows that all variables, namely independence, motivation, and understanding of entrepreneurship have a positive effect on the high interest of Vocational Students to become young entrepreneurs.